ISRAELI–IRANIAN MISSILE TERRITORIAL VIOLATIONS IN THE AIRSPACE OF SYRIA: A REVIEW OF INTERNATIONAL LAW - Kaloko, Ilhamda Fattah; Harmain, Irfan; Adri, Saidil; Putra, Rian Rusmana (Law Faculty of Universitas Bandar Lampung, 2025)
The armed conflict between Israel and Iran, involving cross-border missile launches through Syrian airspace, presents complex challenges under international law. This study analyzes the legal implications of such violations, focusing on state sovereignty, state responsibility, and the justification of force under Article 51 of the UN Charter. Using a normative juridical method, the research evaluates the effectiveness of international legal instruments such as the UN Charter, the 1944 Chicago Convention, and the Articles on Responsibility of States for Internationally Wrongful Acts (ARSIWA) 2001 in addressing modern aerial threats involving third-party states. The findings reveal a legal vacuum regarding the regulation of long-range missiles and armed drones, often exploited by powerful states to avoid accountability. Syria, a neutral state in the Israel-Iran conflict, has suffered civilian casualties and sovereignty violations without effective international legal remedies. Furthermore, the self-defense justifications put forward by both Israel and Iran fail to meet the criteria of necessity and proportionality and infringe upon the principle of non-intervention. The weak response from the international community exacerbated by the UN Security Council’s inaction and ICAO’s limited mandate underscores the urgent need for legal reform. This study advocates for the enhancement of international institutional mandates, the development of additional protocols on aerial warfare, and the ratification of ARSIWA to strengthen legal accountability and protect third-state airspace in armed conflict.